Adoption of e-procurement and value addition to Tanzanian public institutions: A case of Tanzania public institutions - Suleiman, Mohammed A. (Mzumbe University, 2024)
A Dissertation Submitted on Partial Fulfilment of the Requirements Award of the Degree of Masters of Science in Procurement and Supply Chain management (MSc) of Mzumbe University, 2013